ANTONYMIC PAIRS USAGE AS AN EFFECTIVE WAY OF FORMING LEXICAL COMPETENCE (ON THE EXAMPLE OF GERMAN SONG «FRAU MANN» BY GROUP RAMMSTEIN) - Рибалка, Наталя; Барліт, Лілія (Modern engineering and innovative technologies, 2024)
The article is devoted to the study of different approaches that can be used to expand vocabulary in any language. Considerable attention is paid to the use of songs, which allow learning new words and grammatical structures in an unusual but effective wa